Cryptanalysis of Some Hash Functions Based on Block Ciphers and Codes - WU, Hongjun (Institutional Knowledge at Singapore Management University, 2002)
At PKC 2000, Inoue and Sakurai proposed some methods to design hash functions from block ciphers and codes (block codes and convolutional codes). They claimed that their hash functions are secure: 2(d-1)m/2 encryptions are necessary to find a collision, where d and m are the minimal distance of the code and the block size of block cipher, respectively. However, we show in this paper that a collision could be found with about alpha*2m encryptions, where alpha is a small number.